ANALISIS PENDAPATAN USAHATANI JAHE MERAH (ZINGIBER OFFICINALE ROSC) DI DESA INSIL KECAMATAN PASSI TIMUR KABUPATEN BOLAANG MONGONDOW (Farming Income Analysis of Jahe Merah (Zingiber Officinale Rosc) in Insil Village Passi Timur Sub-District Bolaang Mongondow Regency) - Marlon Aloysius Andries; Jenny Baroleh; Theodora M. Katiandagho (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2021)
Insil Village Passi Timur Sub District is one of the village that develop ginger plant supported by its land condition suitable for this plant. Farmers are not aware of the prospects of this plant even though during this pandemic there are many requests of this product from the public.            The objective of this research is to the income of red ginger farming in Insil Village, East Passi Sub District, Bolaang Mongondow Regency. This research was conducted from June to July 2021. The data collected were primary data obtained from direct interviews with red ginger farmers using a questionnaire. Secondary data were obtained from the Insil Village Office, BPP Office and data related to research taken from the internet. Sampling was  purposive sampling where 6 samples from a population of 73 farmers who could be found who harvested in June 2021 when the research took place.             The research results showed that the red ginger farming in Insil Baru Village was profitable in terms of the income of each farmer, which averaged Rp 8,508,166 in one growing season. Therefore, red ginger farming has good prospects as a superior product.